Policy innovation in local jurisdictions: Testing for neighborhood influence in school choice policies - Rincke, Johannes (Public Choice, 2006)
Before making difficult decisions, individuals tend to collect information on decision makers in reference groups. With respect to policy innovations in a decentralized public sector, this may give rise to positive neighborhood influence on adoption decisions. In this paper, U.S. school district data are used to show that decision makers indeed are heavily affected by decision makers in reference groups. The policy innovation under consideration is inter-district public school choice. The results suggest that if a given district's neighbors' expected benefits from adopting school choice policies increase, this substantially increases the original district's probability of adoption. The paper thus supports the view that the diffusion of policy innovations is stimulated by horizontal interaction among local governments.
WiSo-Import:2015-03-26:1715
Keywords: policy innovation; school choice; spatial interaction; neighborhood influence